The Effect of Kinesthetic Learning Style on Students' Motivation and Learning Interest - Yoven Jonivan; Suhirman Suhirman; Saepudin Saepudin (FKIP - Universitas Riau, 2026)
This research is based on the importance of learning styles in the teaching and learning process. Generally, learning styles are divided into three types: visual, auditory, and kinesthetic. However, among these, usually only one learning style tends to dominate in each individual. This study focuses on the kinesthetic learning style, which is characterized by physical activity and movement. The purpose of this study is to determine whether there is an influence of kinesthetic learning style on students’ motivation and interest in learning at SMPN 16 Bengkulu City. This research is a field study using a quantitative associative approach. The sample consisted of 68 respondents, and data collection techniques included observation, documentation, and questionnaires. The hypothesis was tested using simple and multiple regression analysis. The results of the study indicate that there is a significant influence of kinesthetic learning style on students’ motivation and interest in learning Islamic Religious Education at SMPN 16 Bengkulu City.